Treatment of two cases of Fournier's gangrene and review of the literature. (April 2014) - Rubegni, Pietro; Lamberti, Arianna; Natalini, Ylenia; Fimiani, Michele
<x xml:space="preserve">Abstract</x> Fournier's gangrene is a rare polymicrobial necrotising soft tissue infection affecting the perineum and scrotum. It is rapidly progressive, destructive and associated with high morbidity and mortality. Management protocol includes prompt diagnosis, early institution of antibiotic therapy and adequate wound debridement, usually requiring multiple operations. Rapid accurate diagnosis is crucial for successful outcome, while early aggressive surgical intervention together with fluid, hemodynamic and nutritional support and broad-spectrum antibiotics are essential to reduce mortality. Dermatologists are often the first specialist consulted. Two cases of Fournier's gangrene are reported in this report. The aim of the report is to underline the importance of an immediate diagnostic approach to save patients, favoured by a close collaboration among dermatologist, surgeon and urologist.